OBJEK ASESMEN DALAM PERSPEKTIF KURIKULUM 2013 - Siti Nurjanah (Universitas Pakuan, 2021)
ASSESSMENT OBJECTS IN THE PERSPECTIVE OF THE 2013 CURRICULUMIn loading the K13 curriculum, the outline of the learning program and the learning method unit is said to be a routine job. Regarding a material context, although it is not easy, it can still be handled because of course the assignment has been adjusted according to competence. A problem usually arises when looking for agreement in the choice of verbs to state goals in the application of learning. So that the basic competence and achievement indicators in the outline of the learning program are felt to be not quite what is meant by the compilers. So that in a learning process it is necessary to always hold an assessment or evaluation so that a teacher can obtain complete data on the progress of the students' abilities. In addition, evaluation must also be able to describe students' abilities in three domains, namely: cognitive, affective and psychomotor. The purpose of this paper is to attempt to describe the object of assessment in the concept of the 2013 curriculum. Through the literature review, it was found that the object of assessment in the application of the 2013 curriculum contained cognitive, affective and psychomotor theories which all integrated with one another. In a more structured manner the assessment object which includes cognitive, affective and psychomotor in its application in the 2013 curriculum describes the characteristics starting during the teaching and learning process in the hope that before we understand a concept, we must remember it first, before we apply it we must first understand it. Before we analyze, we have to apply it first. Before we evaluate, we have to analyze first. Before we can create or create something, then we have to remember, understand, apply, analyze and evaluate